Strengths and weaknesses in palliative nursing care in pediatrics: an integrative review - Lavôr, Danniele Santos Andrade de; Cândida Pereira, Mayara (JRG Journal of Academic Studies, 2023)
Objective: To investigate, through an integrative literature review, the factors that weaken and enhance nursing care for children in palliative care. Methods: Integrative literature review carried out in the SciELO, LILACS and BDENF databases between june 2021 and April 2022, which generated 517 references. After removing duplicates and applying the inclusion and exclusion criteria, the final sample consisted of 6 articles. Results: The good relationship between nurse, family and child, as well as the active role of the multidisciplinary team and the need to value the child and family in discussions about their care were identified positive aspects. Furthermore, the need to offer humanized care in the development of palliative care for children was highlighted. Conclusion: There is a need to strengthen child health care in palliative care, involving efforts to establish bonds and better communication aimed at the well-being of children and their families.